Ticagrelor could cause central sleep apnea after acute coronary syndrome in patients without left ventricular dysfunction or heart failure. (25th November 2020) - Meurin, P; Ben Driss, A; Defrance, C; Renaud, N; Dumaine, R; Weber, H; Grosdemouge, A; Mouram, S; Pericart, L; Bonnevie, L; Tabet, J.Y
Abstract: Background: Although the prevalence of obstructive sleep apnea (OSA) syndrome is high in patients with acute coronary syndrome (ACS), little is known about central sleep apnea (CSA) in these patients, especially if they have no left ventricular dysfunction (indeed, it is well known that heart failure could be a confounding factor as it is an important cause of CSA). Furthermore, central apnea could be promoted by ticagrelor, a relatively new drug, already known to cause dyspnea (which could modify the apneic threshold) in some patients. Purpose: To investigate the prevalence of central sleep apnea in patients without left ventricular dysfunction after ACS. Methods: Monocentric prospective survey. All consecutive patients within 365 days after ACS were included if they had (1) left ventricular ejection fraction LVEF >45%, (2) no history of heart failure, (3) systolic arterial pulmonary artery pressure <45 mm Hg, and (4) no history of sleep apnea. After inclusion, patients underwent an overnight sleep study with a portable sleep monitor validated to differentiate central and obstructive apneas. Patients were then classified as "normal" patients if they had an AHI (apnea hypopnea index) <15, "CSA patients" if they had an AHI >15 with a majority of central sleep apneas and "OSA patients" if they had an AHI >15 with a majority of obstructive sleep apneas. Results: Between January 2018 and January, 2020, we included 115 consecutive patients (age 56.1±10.5, male 84%, mean body mass index 28.4±4.5, LVEF: 56±4%). Sleep study was performed 68±62 days (7–350 days) after ACS on average. All of the patients were receiving a single or (mostly) dual antiplatelet therapy: aspirin (n=114: 99%, ticagrelor (n=80: 69.5%), clopidogrel (n=28: 24%), prasugrel (n=4: 3.5%). Finally 80 patients were taking ticagrelor, while 35 were not. A total of 49/115 patients (42.6%) had a clinically significant (moderate to severe) sleep disordered breathing, with an AHI>15: (CSA: n=27/115: 23.5%, OSA:n=22/115: 19%). Among them, 25/115 patients (22%) had a severe (AHI >30) sleep disordered breathing: CSA 12% OSA: 10%. Among patients receiving ticagrelor, 24/80 (30%) had a CSA with an AHI >15, while, in patients not taking ticagrelor only 3/35 (8.5%) had CSA with an AHI >15 (p=0.04) Conclusion: As expected, OSA is frequent after ACS, as in all types of coronary artery disease patients. High prevalence of CSA was less expected and seemed to be correlated with ticagrelor administration. This monocentric survey is a preliminary safety signal. Further studies are needed to investigate the exact incidence, the sustainability and the potential consequences of ticagrelor induced central sleep apnea. Funding Acknowledgement: Type of funding source: None